2021
DOI: 10.3389/fpsyg.2021.660740
|View full text |Cite
|
Sign up to set email alerts
|

Social Media, Depressive Symptoms and Well-Being in Early Adolescence. The Moderating Role of Emotional Self-Efficacy and Gender

Abstract: The study of the psychological effects of social media use on adolescents’ adjustment has long been the focus of psychological research, but results are still inconclusive. In particular, there is a lack of research on the positive and negative developmental outcomes and on possible moderating variables, especially concerning early adolescence. To fill these gaps in literature, the present study longitudinally investigated the relationships between social media use, depressive symptoms, affective well-being an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
2
9
0
1
Order By: Relevance
“…There was a significant difference in the level of regulatory emotional self-efficacy between males and females. More specifically, the level of regulatory emotional self-efficacy of males was significantly higher than that of females, which was consistent with the results of previous studies ( Calandri et al, 2021 ). Compared with females, males showed more confidence in dealing with negative emotions and were socially conditioned to respond with silence or positive emotions ( Putwain and Daly, 2014 ; Wu, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…There was a significant difference in the level of regulatory emotional self-efficacy between males and females. More specifically, the level of regulatory emotional self-efficacy of males was significantly higher than that of females, which was consistent with the results of previous studies ( Calandri et al, 2021 ). Compared with females, males showed more confidence in dealing with negative emotions and were socially conditioned to respond with silence or positive emotions ( Putwain and Daly, 2014 ; Wu, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the issue of causality in the relationship between self-efficacy and depressive symptoms is debated, and cyclical relationships are also viable. Previous studies have found that self-efficacy moderated associations between social media use and mental health (36,37). Similarly, our study showed that general self-efficacy significantly moderated two of the associations between negative social media-related experiences and depressive symptoms.…”
Section: Factors Associated With Depressive Symptomssupporting
confidence: 84%
“…Among young people, psychological resource factors such as general self-efficacy have been associated with favorable mental health outcomes in several studies over the last decades (33)(34)(35). In addition, self-efficacy has been found to moderate associations between various aspects of social media use and mental health, indicating that associations between more social media use and poorer mental health may be stronger for people with low self-efficacy (36,37). Thus, while self-efficacy in adolescents may be vulnerable to the influence from social media, self-efficacy may also be viewed as a psychological resource that can buffer against a potentially negative influence from social media on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, individuals with high regulatory emotional self-efficacy are less likely to resort to problematic social media use for psychological satisfaction. The reason is that they can successfully manage their emotions ( 66 ) even when they are experiencing high fear of missing out. Individuals with high regulatory emotional self-efficacy, even if they suffer anxiety, fear, and other emotions, are more confident to deal with these negative emotions ( 95 , 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…As individuals feel more stress, psychological needs in their lives are not met, but individuals with higher levels of emotion management abilities leave individuals with lower needs for desired compensation which lead to less problematic social media use behaviors ( 65 ). Furthermore, as the fear of missing out rises, individuals in their lives are at a lower risk of tending to use mobile social media due to higher emotional management abilities ( 66 ). Then, potentially harmful results (problematic social media use) might be reduced by the combination of protective (regulatory emotional self-efficacy) and risk (stressors of COVID-19, fear of missing out) variables that interact.…”
Section: Introductionmentioning
confidence: 99%